Post-Cesarean Wound Healing Outcomes Among Women With Diabetes Mellitus: A Scoping Review - Diva Peni Agustin Widihastuti; Faizah Betty Rahayuningsih (Madago Nursing Journal, 2026)
ABSTRACT Background: Diabetes mellitus contributes to impaired postoperative wound healing following cesarean section and increases the risk of surgical site infection, wound dehiscence, and delayed recovery. However, evidence regarding wound healing outcomes among diabetic women following cesarean section remains limited, particularly concerning implications for maternal nursing care. Therefore, this scoping review aimed to map the available evidence regarding postoperative wound healing outcomes following cesarean section among women with diabetes mellitus. Methods: This study employed a scoping review design following the Joanna Briggs Institute (JBI) framework and PRISMA-ScR guidelines. Literature searches were conducted in PubMed, SpringerLink, and ScienceDirect databases for studies published between 2021 and 2025. Screening and eligibility assessment were independently conducted by two reviewers using predefined inclusion and exclusion criteria. Five studies met the eligibility criteria and were included in the final synthesis. Results: The reviewed studies consistently demonstrated that diabetes mellitus was associated with unfavorable postoperative recovery outcomes and increased wound-related complications after cesarean section. The most frequently reported complications included surgical site infection, delayed wound healing, wound dehiscence, and impaired scar healing. Poor perioperative glycemic control emerged as an important contributing factor associated with adverse postoperative recovery outcomes. Conclusion: Diabetes mellitus significantly affects postoperative wound healing following cesarean section and increases the risk of wound-related complications. Comprehensive perioperative management and continuous maternal nursing care may contribute to improved postoperative recovery and reduced wound-related complications among women with diabetes mellitus. KEYWORDS: Cesarean section; Diabetes mellitus; Postoperative wound healing; Surgical site infection; Wound healing